[OP.8B.06] HYPOTENSIVE THERAPY IN PATIENTS WITH OBSTRUCTIVE SLEEP APNOEA. (September 2016) - Talarowska, P.; Segiet, A.; Rozanska, M.; Mozenska, O.; Kosior, D.A.
Abstract : Objective: Obstructive sleep apnea (OSA) is the most common sleep-related breathing disorder. Individuals with OSA are at increased risk of cardiovascular diseases such as arterial hypertension (HTN), heart failure, stroke and pulmonary hypertension. Detailed data regarding hypotensive therapy and its effectiveness in patients with HTN and OSA are lacking. The aim of the study was to characterize in details hypotensive therapy in patients with HTN and OSA. Design and method: We retrospectively analyzed 1270 patients who were treated in our outpatient sleep apnea clinic. All patients underwent polysomnography. 795 patients with diagnosed HTN were included in further analysis. In the next step we divided patients in 2 subgroups with and without OSA. Local ethics committee gave consent to conduct the study. Results: In our study population mean age was 60.1 ± 11.4 years, 69.4% were male, 64.9% were smokers, 63% were obese, 65% had hyperlipidemia, 59.9% reported snoring, and 83.4% had the diagnosis of OSA (average supine AHI 46, 8 ± 35, 2). Patients with OSA were statistically significantly older (p = 0.033), were more frequently male (p < 0.001), obese (p < 0.001) and more often had hyperlipidemia (p < 0.001). Regarding details of hypotensive therapy patients with OSA significantly more frequently took ACEi, ARBs, betablockers, thiazides and loop diuretics, aldosteron antagonists, calcium channel blockers and alpha blockers (p < 0.01 for all medication groups). We found no statistically significant differences in respect of potassium sparing diuretics and hypotensive drugs acting centrally. We found no statistically significant differences between patients with and without OSA if analyzing use of different medication within each class of hypotensive drugs. Conclusions: There are significant differences in antyhypertensive therapy in patients with HTN and with or without OSA. Since HTN is one of the most recognized comorbidity in patients with OSA further studies are needed in order to assess effectiveness of hypotensive therapy in this population.